PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN HAND HYGIENE DI SDN TONDO - Siti Marwah; Elifa Ihda Rahmayanti; Maharani Farah Dhifa Dg. Masikki (KEWINUS: Jurnal Keperawatan dan Kesehatan, 2025)
Background: Hand hygiene is an important step in preventing infection, but the children's knowledge to practice it still low, especially in areas with limited access to health education. The preliminary studies at SDN Tondo showed that most students did not understand or consistently perform proper hand washing. This study aims to analyze the impact of health education in improving students' knowledge regarding hand hygiene as an effort to encourage clean living behavior and disease prevention. Methods: This type of research is quantitative with pre-experimental using a one group pre-test post-test design. The total of population in this study were 113 students in fourth and fifth grade, and sample taken by using purposive sampling technique. Research Results: Univariate analysis showed that before being given health education found that the level of knowledge of 17 respondents (52.8) was poor and 14 respondents (45.2) was moderate knowledge level and the level of knowledge after being given health education about 30 respondents (96.8%) was good knowledge level and 1 respondent (3.2%) was moderate knowledge level. Wilcoxon test on bivariate analysis shows that there is an impact of health education toward the level of knowledge of hand hygiene (p-value = 0.00, alpha = 0.05). Conclusion: There is an impact of health education toward the level of hand hygiene knowledge in SDN Tondo. Suggestion: This study encourages the integration of hand hygiene education in the curriculum, improvement of hygiene facilities at SDN Tondo, and teacher training. For further researchers can explore alternative educational methods and the long-term impact on student behavior. Key words: Hand Hygiene, Schoolgirls, Knowledge Level